Mesenchymal Stem-Cell-Derived Exosomes and MicroRNAs: Advancing Cell-Free Therapy in Systemic Sclerosis - Cristiano Barbetta; Francesco Bonomi; Gemma Lepri; Daniel E. Furst; Silvia Bellando Randone; Serena Guiducci (Cells)
Mesenchymal stem cell (MSC) transplantation has emerged as a potential therapeutic strategy for systemic sclerosis (SSc), a rare autoimmune disease characterized by inflammation, fibrosis, and vasculopathy. Recent evidence suggests that the therapeutic benefits of MSCs do not depend directly on their ability to proliferate but rather on their capacity to release extracellular nanovesicles known as exosomes (MSC-Exos). MSC-Exos are rich in bioactive molecules such as microRNAs, which can modulate gene expression and trigger significant biological responses, playing a central role in modulating immune responses, inhibiting fibrotic pathways and promoting tissue repair and angiogenesis. Preclinical studies have demonstrated that MSC-Exos can attenuate fibrosis, modulate macrophage polarization, suppress autoreactive lymphocyte activity, and even reverse pulmonary arterial hypertension in animal models of SSc. Compared to cell-based therapies, MSC-Exos offer several advantages, including lower immunogenicity and better safety profile. This review provides an overview of the immunomodulatory, antifibrotic, and angiogenic properties of MSC-Exos and explores their potential as novel cell-free therapy for SSc.